Faking Good: An Investigation of Social Desirability and Defensiveness in an Inpatient Sample With Personality Disorder Traits. Issue 3 (4th May 2019) - Williams, Margot M.; Rogers, Richard; Sharf, Allyson J.; Ross, Colin A.
ABSTRACT: Accurate interpretations of psychological assessments rely heavily on forthright reporting. However, researchers and practitioners recognize that examinees can easily invalidate their test results by underreporting symptoms or overstating positive attributes. Rogers (2008) delineated two distinct but related forms of positive impression management (PIM): defensiveness (denying symptoms and psychological impairment) and social desirability (putting forth an exaggeratedly positive image). Although these two have often been combined in past research, this study sought to investigate each separately via a mixed within- and between-subjects simulation design. Simulation scenarios included a special rehabilitation program for the defensiveness (DF) condition and a competitive job for social desirability (SD). The study used the Personality Inventory for DSM–5 (PID–5; Krueger, Derringer, Markon, Watson, & Skodol, 2012) and recruited 106 inpatients from a psychiatric hospital. As expected, inpatients with prominent personality traits substantially suppressed them under both PIM conditions. Having shown the susceptibility of the PID–5 to intentional distortion, two empirically derived and conceptually based validity scales were next developed to address this important concern. Pending further validation, they might contribute to screening PIM presentations, thus promoting the PID–5's clinical utility. Continued research is needed across multiscale inventories for differentiating PIM presentations.